Avaliação das situações das Áreas de Preservação Permanente no estado de São Paulo - Costa, Vinicius Moura (Universidade Federal de São Carlos, 2022)
Permanent Protection Areas (PPA) are protected by the Native Vegetation Protection Law (NVPL – Law 12.651/2012), however, these areas are historically used for other purposes, and, therefore, not necessarily have forest cover or native non-forest vegetation. This study intended to understand the dynamics of change in land use/land cover (LULC), from 1985 to 2020, in PPAs of hydric, altitude and declivity types, in the state of São Paulo, considering article 4º of NVPL. Hereof maps and tables of declivity and altitude PPAs were produced through Digital Elevation Model (DEM) of São Paulo, and additionally to hydric APPs provided by the Brazilian Foundation for Sustainable Development (FBDS). Furthermore, LULC and Change Transition data were used between the years 1985 to 2020, provided by MapBiomas. The results pointed out that between 1985 and 2020 there was a reduction of 88.6 thousand hectares of natural formations throughout the State, as follows, in 2020, occupied 22.48%. The main transition of natural formations was due to agriculture and silviculture expansion (1.089 million hectares). Even so, there was the emergence of new forests on a scale of 1.07 million hectares, with agriculture and silviculture being the LULC class that most gave way to natural formations, and this change from agriculture to natural formations may be due to the abandonment of areas of low interest for agricultural purposes. The studied PPAs occupy about 11.8% of the State, however, in 2020 only 52.36% were covered by natural formations, this number was 46.87% in 1985. Consequently, today the residual of these PPAs were occupied by agriculture, livestock and silviculture (45.31%); anthropized areas (1.57%); and water bodies (0.77%). The transitions of change within the PPAs occurred on a larger scale between natural formations and agriculture and silviculture, where natural formations ceded 132.9 thousand hectares to agriculture and silviculture, while it also became to occupied 280.6 thousand hectares of agriculture and silviculture. Analyzing the PPAs in a regionalized way, by municipality, it was observed that the municipalities in the central-south and central-east regions showed a higher percentage of their territories occupied by PPAs. The southern (Vale do Ribeira) and eastern (Mantiqueira region) regions transacted mainly between agriculture and livestock for natural formation; and natural formation for agriculture and silviculture. In the eastern and western/northwestern areas of the state, agricultural use within the PPAs remained without changes between the years analyzed. In relation to urban structures, in PPAs, these advanced over agricultural areas and natural formations. Finally, it was noted that the dynamics of change between natural formations and agriculture and silviculture occurred from one to the other. Regarding non-natural occupations inserted in PPAs, these are not necessarily illegal, as the NVPL recognizes the consolidated use, establishing mechanisms of mandatory restoration strips and there are laws that allow the intervention and suppression of vegetation under specific conditions.
Assessment of the situations of Permanent Preservation Areas in the state of São Paulo
Keywords: Lei de Proteção da Vegetação Nativa; Áreas Protegidas; Uso e Cobertura do Solo; Formações Naturais; Native Vegetation Protection Law; Protected Areas; Land Use/Land Cover; Natural Formations; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL